Whole Genome Sequencing of Pediatric Klebsiella pneumoniae Strains Reveals Important Insights Into Their Virulence-Associated Traits - Flores-Valdez, Mauricio; Ares, Miguel A.; Rosales-Reyes, Roberto; Torres, Javier; Girón, Jorge A.; Weimer, Bart C.; Mendez-Tenorio, Alfonso; De la Cruz, Miguel A. (Frontiers in Microbiology, 2021)
Klebsiella pneumoniae is recognized as a common cause of nosocomial infections and outbreaks causing pneumonia, septicemia, and urinary tract infections. This opportunistic bacterium shows an increasing acquisition of antibiotic-resistance genes, which complicates treatment of infections. Hence, fast reliable strain typing methods are paramount for the study of this opportunistic pathogen’s multi-drug resistance genetic profiles. In this study, thirty-eight strains of K. pneumoniae isolated from the blood of pediatric patients were characterized by whole-genome sequencing and genomic clustering methods. Genes encoding β-lactamase were found in all the bacterial isolates, among which the blaSHV variant was the most prevalent (53%). Moreover, genes encoding virulence factors such as fimbriae, capsule, outer membrane proteins, T4SS and siderophores were investigated. Additionally, a multi-locus sequence typing (MLST) analysis revealed 24 distinct sequence types identified within the isolates, among which the most frequently represented were ST76 (16%) and ST70 (11%). Based on LPS structure, serotypes O1 and O3 were the most prevalent, accounting for approximately 63% of all infections. The virulence capsular types K10, K136 and K2 were present in 16, 13 and 8% of the isolates, respectively. Phylogenomic analysis based on virtual genome fingerprints correlated with the MLST data. The phylogenomic reconstruction also denoted association between strains with a higher abundance of virulence genes and virulent serotypes compared to strains that do not possess these traits. This study highlights the value of whole-genomic sequencing in the surveillance of virulence attributes among clinical K. pneumoniae strains.